Hypophosphatemia associated risk factors in pediatric intensive care patients - Şan, Emine Sibel; Erdoğan, Seher; Boşnak, Mehmet; Şan, Murat (The Turkish Journal of Pediatrics, 2017)
The aim of this work is to determine the prevalence and risk factors of hypophosphatemia in pediatric patients admitted to intensive care unit. The study was performed prospectively in patients admitted to the Pediatric Intensive Care Unit between June 2014 and December 2014. Fifty-seven patients were included in the study. The mean age of the study population was 24 months (2-192 months); 25 patients (43.9%) were male and 32 were female (56.1%). The mean body weight z-score was -1.47 ± 2.23, and 23 (40.4%) patients had malnutrition. On admission 16 (28.1%) patients had hypophosphatemia. There were no statistically significant differences between the hypophosphatemic patient group and normophosphatemic patient groups in terms of demographic and clinical characteristics. There were also no significant differences between the two groups in terms of risk factors. Potassium and creatinine levels were significantly lower in the hypophosphatemic group, compared to the normophosphatemic group. According to a multivariate logistic regression analysis, risk factors for hypophosphatemia were low potassium level (OR: 16.76; 95% CI: 2.09 - 134.72; p: 0.008), malignant solid tumors (OR: 52.40; 95% CI: 2.04 - 1,344.32; p: 0.017, p: 0.036). and female gender (OR: 6.18; 95% CI: 1.12 - 34.00; p: 0.036). Prospective studies with larger sample size should be conducted to study the prevalence and risk factors of hypophosphatemia at pediatric intensive care unit.
Keywords: hypophosphatemia; intensive care unit; total parenteral nutrition